The solution of third order ordinary differential equations using adomian decomposition method and variational iteration method / W. Khairiyah Hulaini Wan Ramli …[et al.] - Wan Ramli, W. Khairiyah Hulaini; Hamdan, Nur Iffah Zulaikha; Ruslan, Nur Ain Dayana; Mohamad Asri, Nur Aisyah; Abdul Manaf, Zati Iwani; Md Nor, Norlaila; Fauzi, Farahanie (Universiti Teknologi MARA, Kelantan, 2023)
Solving ordinary differential equations (ODE) is crucial in physics, engineering, and mathematics. Adomian decomposition method (ADM) and variational iteration method (VIM) are two of many methods in solving ODE. Both techniques involve constructing the required iterative or recurrence formulas based on the equation under consideration and additional requirements, allowing the identification of succeeding iterations of a series or sequence approximately matching to solve the third order ODE. In this study, ADM and VIM will be used in solving homogenous and nonhomogeneous third order ordinary differential equations and analysis on method of solutions will be discussed. Overall, it is identified that both methods are efficient in solving linear third order ordinary differential equations.